PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI KERAGAMAN BUDAYA DI INDONESIA UNTUK PESERTA DIDIK KELAS IV SD NEGERI 1 BAJULAN - Lusi Andriani; Kharisma Eka Putri; Alfi Laila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the results of observations and interviews with fourth-grade teachers, as well as survey results from teachers and students in the fourth grade, which indicated that there were issues with the use of learning media in the classroom. In the learning process, teachers primarily employed lecture-based methods and tended to rely on textbooks as teaching tools. The consequence of this issue was that most students struggled to comprehend the learning material, particularly regarding cultural diversity in Indonesia. The researcher used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The data analysis techniques used were qualitative and quantitative methods. The product developed is an Android-based interactive multimedia. Based on expert validation, the material received a score of 96%, while the media received a score of 91% in the “Very Valid” criteria. The practicality test results from the teacher response questionnaire received a score of 94%, while the student response questionnaire received a score of 91.66%, thus meeting the “Very Practical” criteria. The results of the effectiveness test of the students' post-test scores with classical learning completeness obtained 94.44% of all students achieving scores above the minimum passing grade, with 17 students successfully obtaining a passing score, indicating that the media was “Very Effective”. The conclusion from this study is that the development of interactive multimedia based on Android for cultural diversity material in Indonesia for fourth-grade students at SD Negeri 1 Bajulan meets the criteria of validity, practicality, and effectiveness for use.